Estrategias metodológicas para mejorar el proceso de aprendizaje de la cinemática, en los estudiantes de primer año de bachillerato general unificado de la unidad educativa Calasanz, período 2012-2013. Lineamientos alternativos - Reyes Benitez, Katherine Yesenia (2014)
The present research work has been carried out in order to identify " METHODOLOGICAL STRATEGIES TO IMPROVE THE LEARNING PROCESS OF KINEMATICS IN FIRST YEAR STUDENTS GENERAL UNIFIED HIGH SCHOOL EDUCATION UNIT CALASANZ , PERIOD 2012-2013 " , highlighting the methods and techniques coadyuden to improved student learning, and to improve the educational process . The specific objectives are designed to determine the methods and techniques used by teachers of physics in teaching kinematics, determine the level of student learning and develop alternative guidelines to improve the teaching-learning process of the kinematics, in the first General Unified School year, Calasanz Education Unit, the city of Loja. The main results can be mentioned the following: The teacher uses inductive methods, analog or comparative asset, heuristic and analytical techniques used as reading, underline, demonstrations, problems, exhibitions, brainstorming, concept maps and discussion; within the teaching- learning process kinematics. Likewise states that the students' academic level is high. Moreover students indicate that the teacher uses deductive methods, analog or comparative assets and analytic and technical reading, demonstrations, problems, diagrams and discussion and has a medium level of learning about kinematics. We must say, finally, that as a result of research conducted methodological strategies are proposed to improve the learning process of the kinematics, given the need for teachers to innovate and enrich their learning processes.